2022
DOI: 10.1093/neuonc/noac132
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional study of the frequency, genomic landscape, and outcome of IDH-mutant glioma in pediatrics

Abstract: Background The incidence and biology of IDH1/2 mutations in pediatric gliomas are unclear. Notably, current treatment approaches by pediatric and adult providers vary significantly. We describe the frequency and clinical outcomes of IDH1/2-mutant gliomas in pediatrics. Methods We performed a multi-institutional analysis of the frequency of pediatric IDH1/2-mutant gliomas, identified by next-generation sequencing (NGS). In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…They also tend to be tumors seen in older children or early adulthood, which is not a characteristic of our group. 23 According to Yeo et al, 24 there could be 9% IDH mutant adult-type gliomas in our study, but that does not affect the importance of the MMR status of the tumors. Suwala et al 25 have suggested that primary dMMR IDH mutant astrocytoma have the worst clinical outcome.…”
Section: Discussionmentioning
confidence: 49%
“…They also tend to be tumors seen in older children or early adulthood, which is not a characteristic of our group. 23 According to Yeo et al, 24 there could be 9% IDH mutant adult-type gliomas in our study, but that does not affect the importance of the MMR status of the tumors. Suwala et al 25 have suggested that primary dMMR IDH mutant astrocytoma have the worst clinical outcome.…”
Section: Discussionmentioning
confidence: 49%
“…While category (1) is beyond the scope of this review, it is understood that there are no firm age cutoffs for either the adult-type or pediatric-type tumors. For example, isocitrate dehydrogenase (IDH) mutant diffuse gliomas are not exclusive to adult patients, and conversely, some diffuse gliomas in adults can have pediatric-type molecular features [12, 13].…”
Section: Changes In Tumor Categorization and Nomenclaturementioning
confidence: 99%
“…The role of IDH1 mutations in the natural history of pLGGs remains unclear. A recent case series found that patients with IDH1-mutant pLGGs had excellent short-term survival, but 5-year progression-free survival (PFS) was 42.9%, with glioma-related mortality after 10 years [31] .…”
Section: Introductionmentioning
confidence: 99%